The Pakistan Cauldron : Conspiracy, Assassination & Instability - Farwell, James P.; Foreword by Duffey, Joseph D. (New Delhi Pentagon Press, 2012)
The killing of Osama bin Laden spotlighted Pakistan?s unpredictable political dynamics, which are often driven by conspiracy theories, paranoia, and a sense of betrayal. In Pakistan, the late prime minister Benazir Bhutto famously declared that there is ?always the story behind the story.? In The Pakistan Cauldron, James P . Farwell explains what makes Pakistani politics tick. Farwell has advised the Department of Defense on terrorism, sovereignty, and the political issues in the Middle East, Africa, and Pakistan. Here he reveals how key Pakistani political players have inconsistently employed the principles of strategic communication to advance their agendas and undercut their enemies. Pakistan is an enigma to many. Only by understanding the complex forces that shape Pakistani leaders can we uncover their shifting political agendas and how they affect America and the West. Farwell explains how and why former president Pervez Musharraf clamped down on nuclear scientist A. Q. Khan and isolated him.
Include Index and Notes.
Keywords: Political Leadership -- Communication in Politics -- Khan, A. Q. -- (Abdul Qadeer), -- 1936-